Comparison of joint kinematics from optical marker-based and inertial sensor-based motion capture during change-of-direction movements - Mareike Kühne; Peter Federolf; Diego Jaén-Carrillo; Katharina Schiel; Maurice Mohr (Current Issues in Sport Science, 2024)
The development of inertial measurement units (IMUs) has opened up possibilities to test kinematics of sports movements in natural environments (Di Paolo et al., 2023). This advantage over lab-based optical motion capture (OMC) comes at the cost of inherent inaccuracies. Especially, fast multidirectional movements including de- and accelerations pose a challenge for inertial-based movement reconstruction with limited task-specific validation research available (Heuvelmans et al., 2022). Therefore, we aimed to test the validity of IMU-based kinematics in a 180° change of direction (COD) task to provide insight into the applicability for future on-field ACL injury risk research.